Intelligentes Gesamtmaschinenmanagement für elektrische Antriebssysteme - Pohlandt, Christian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2018)
Innovative electric propulsion systems are increasingly applied to off-highway machines, to gain efficiency optimization of the work process. This book focuses on the aspect of work process optimization and achieves forward-looking results through the use of intelligent, adaptive overall machine management.